What is cardiogenic shock? New clinical criteria urgently needed - Ostadal, Petr; Belohlavek, Jan (Current opinion in critical care, 2024)
PURPOSE OF REVIEW: Cardiogenic shock is a clinical syndrome with different causes and a complex pathophysiology. Recent evidence from clinical trials evokes the urgent need for redefining clinical diagnostic criteria to be compliant with the definition of cardiogenic shock and current diagnostic methods. RECENT FINDINGS: Conflicting results from randomized clinical trials investigating mechanical circulatory support in patients with cardiogenic shock have elicited several extremely important questions. At minimum, it is questionable whether survivors of cardiac arrest should be included in trials focused on cardiogenic shock. Moreover, considering the wide availability of ultrasound and hemodynamic monitors capable of arterial pressure analysis, the current clinical diagnostic criteria based on the presence of hypotension and hypoperfusion have become insufficient. As such, new clinical criteria for the diagnosis of cardiogenic shock should include evidence of low cardiac output and appropriate ventricular filling pressure. SUMMARY: Clinical diagnostic criteria for cardiogenic shock should be revised to better define cardiac pump failure as a primary cause of hemodynamic compromise.
Keywords: srdeční zástava; Humans; Hemodynamics; Shock, Cardiogenic; Heart Arrest; hemodynamika; kardiogenní šok; lidé